FRI0146 Levels of ultrasensitive troponin and nt-probnp in rheumatoid arthritis. (23rd January 2014) - Avouac, J.; Meune, C.; Gobeaux, C.; Borderie, D.; Lefevre, G.; Kahan, A.; Dieude, P.; Allanore, Y.
Abstract : Background: Patients with rheumatoid arthritis (RA) experience premature mortality that is largely due to cardiovascular disease (CVD). Selective biomarkers have been proposed for CVD prediction. Indeed, ultrasensitive troponin (hs-cTn), a biomarker of myocardial injury, and NT-proBNP, a marker of myocardial dysfunction, have been recently identified as predictors of increased cardiovascular (CV) mortality, both in patients with diagnosed ischemic heart disease and in the general population. Objectives: Our aim was to measure hs-cTn and NT-proBNP in RA patients and to examine associated factors with increased concentrations of these biomarkers. Methods: The plasma hs-cTn concentrations were measured using an electrochemiluminescence immunoassay (Roche Diagnostic, Meylan, France). The 99th percentile, with a CV ≤10% was achieved for 14 ng/L. Plasma NT-proBNP levels were assessed by an immunoenzymatic assay (Roche Diagnostic). Concentrations of these biomarkers were measured in consecutive RA patients and age- and gender-matched healthy controls. Results: 236 consecutive RA patients were included (192 females, 81%) with a mean ± standard deviation, SD, age of 57±13 years and a mean ±SD disease duration of 15±10 years; 79% had radiographic erosions, 79% positive rheumatoid factors and 84% positive anti-CCP antibodies. The mean±SD DAS28 was 3.7±1.4 (116 patients, 49%, with DAS28 >3.2 and 33, 14%, with DAS28 >5.1). At the time of the dosage, 189 (80%) patients received corticosteroids (mean±SD dose 7.1±3.2 mg/day), 200 (85%) a conventional DMARD, and 146 (62%) a biologic agent. We also included 213 controls (165 females, 77%), with a mean±SD age of 54±15 years. RA patients had increased hs-cTn concentrations (5.8±10.1 ng/l vs. 4.1±3.2 ng/l, p=0.02) and NT-proBNP levels (187±441 ng/l vs. 76±259 ng/l, p=0.001) compared to controls. These results remained consistent after stratification for CV risk factors by multivariate linear regression. Hs-cTn and NT-proBNP levels were correlated in RA patients (r=0.34, p<0.0001). RA patients with C-reactive protein (CRP) >10 mg/l and a DAS28 >5.1 were more likely to have higher hs-cTn concentrations (respectively 5.9±7.1 ng/l vs. 4.3±3.6 ng/l, p=0.03, and 10.7±23.1 ng/l vs. 5, 3±8, 4 ng/l, p= 0, 02). In addition, patients with increased hs-cTn levels (>14 ng/l) were more likely to have a DAS28 >5.1 (p=0.03). hs-cTn levels were not associated with CV risk factors, the presence of radiographic erosions, treatment received or autoantibody status. No association was identified between NT-proBNP levels and CV risk factors or RA disease characteristics. Conclusions: hs-cTn concentrations are increased in patients with RA, independent of CV risk factors. Our results showed for the first time an association between increased hs-cTn concentrations, CRP levels and high RA disease activity, which support the link between myocardial injury and inflammation. Increased hs-cTn in RA may indicate subclinical, indolent myocardial injury, which may be related to myocardial dysfunction, supported by increased NT-proBNP levels. Further studies are now necessary to study the merit of hs-cTn to predict CVD in RA. Disclosure of Interest: None Declared